Shipper economic demand function for cargo port services: A note. (February 2023) - Talley, Wayne K.; Ng, ManWo
Highlights: Critical relationship in cargo handling at seaports is the shipper economic demand function. Rigorously derives shipper economic demand function for cargo port services. The price elasticity of demand for port services by users of port services also derived. Abstract: An important relationship in cargo handling at cargo ports is the shipper economic demand function for cargo port services, which relates the demand for cargo port services to the prices charged by cargo ports and the cargo demand from shippers at other cargo ports. To our knowledge, such a function has heretofore not been rigorously derived in the maritime economics literature. This note derives a shipper economic demand function for cargo port services to be provided for shipper cargoes while in a cargo port. Using the demand function, it is shown how the price elasticity of demand for port services by users of port services can be derived.